Kepedulian Masyarakat Pedesaan dalam Upaya Mencegah Penyebaran Covid-19: Studi Kasus di Dua Desa Aceh Besar - Rizka Febryani, Dwi; Rahmi, Zulfia; Ibrahim, Lukman (Jurnal Riset dan Pengabdian Masyarakat, 2021)
This research aims to describe the attitudes in preventing the spread of Covid-19 of the villagers of Gampong Lampuuk and Gampong Cot Suruy, Aceh Besar. It uses a case study of the qualitative approach. Data is collected by using observation and interview techniques and analyzed by using the thematic technique. There are positive responses from the community who received counseling on the prevention of Covid-19, although the level of public concern about Covid-19 was low due to the distrust of the existence of the Corona virus. Followed the World Health Organization (WHO) declaration of the existence of Covid-19 as a pandemic on March 11, 2020, The Indonesian government issued some regulations related to preventing the spread of Covid-19. The realization of each regulation involves the central government, local government, head of the villagers, and the whole society. Specifically, The head of the villagers (Geuchik) and health workers mobilize outreach activities to prevent the pandemic. In fact, not all people are willing to apply health protocols for preventing the spread of the disease.